Latitudinal Change of Tropical Cyclone Maximum Intensity in the Western North Pacific - Jae-Won Choi; Yumi Cha; Hae-Dong Kim; Sung-Dae Kang (Advances in Meteorology)
This study obtained the latitude where tropical cyclones (TCs) show maximum intensity and applied statistical change-point analysis on the time series data of the average annual values. The analysis results found that the latitude of the TC maximum intensity increased from 1999. To investigate the reason behind this phenomenon, the difference of the average latitude between 1999 and 2013 and the average between 1977 and 1998 was analyzed. In a difference of 500 hPa streamline between the two periods, anomalous anticyclonic circulations were strong in 30°–50°N, while anomalous monsoon trough was located in the north of South China Sea. This anomalous monsoon trough was extended eastward to 145°E. Middle-latitude region in East Asia is affected by the anomalous southeasterlies due to these anomalous anticyclonic circulations and anomalous monsoon trough. These anomalous southeasterlies play a role of anomalous steering flows that make the TCs heading toward region in East Asia middle latitude. As a result, TCs during 1999–2013 had higher latitude of the maximum intensity compared to the TCs during 1977–1998.